2017
DOI: 10.18632/oncotarget.22334
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of regorafenib and sorafenib in preclinical models of hepatocellular carcinoma

Abstract: The purpose of this study was to investigate the antitumor activity of regorafenib and sorafenib in preclinical models of HCC and to assess their mechanism of action by associated changes in protein expression in a HCC-PDX mouse model. Both drugs were administered orally once daily at 10 mg/kg (regorafenib) or 30 mg/kg (sorafenib), which recapitulate the human exposure at the maximally tolerated dose in mice.In a H129 hepatoma model, survival times differed significantly between regorafenib versus vehicle (p=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…3,4 The broader approach used in this study is not only biologically warranted considering the heterogeneity of HCC tumors, 15,27 but is also needed due to the multiple targets and pathways affected by MKIs such as regorafenib. 7 Recent protein expression analysis of regorafenib and sorafenib has revealed a complex and distinct pattern of protein expression, which may provide some rationale as to why regorafenib is active in sorafenib-refractory patients. Disease heterogeneity and multikinase inhibition also make it perhaps unlikely that a single target will be identified that can predict treatment benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The broader approach used in this study is not only biologically warranted considering the heterogeneity of HCC tumors, 15,27 but is also needed due to the multiple targets and pathways affected by MKIs such as regorafenib. 7 Recent protein expression analysis of regorafenib and sorafenib has revealed a complex and distinct pattern of protein expression, which may provide some rationale as to why regorafenib is active in sorafenib-refractory patients. Disease heterogeneity and multikinase inhibition also make it perhaps unlikely that a single target will be identified that can predict treatment benefit.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Protein expression analyses in an HCC preclinical model have confirmed a complex expression pattern with regorafenib that is different from that of sorafenib. 7 This complex pattern, along with disease heterogeneity, may make the identification of biomarkers challenging.…”
Section: Background and Aimsmentioning
confidence: 99%
“…However, the prognosis for patients with unresectable advanced-stage HCC remains poor (6,7). Sorafenib was the only systemic drug available for treating advanced HCC until the recent approval of regorafenib, another multi-kinase inhibitor (8,9). However, sorafenib and regorafenib have a low durable response rate and their benefit for survival is limited (10).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the acidic environment of HCC tissue, the copolymer studied herein might be further slightly modified to generate acid‐cleavable non‐ionic surfactants targeting its delivery to the tumour, and hence, increasing the efficacy and selectivity of the antitumoral treatment, and lowering individual and cumulative anthracycline doses. Likewise, it is tempting to speculate that this general phenomenon might also occur with recently proposed HCC systemic therapeutics (such as regorafenib, approved by FDA in 2017) …”
Section: Discussionmentioning
confidence: 98%
“…Likewise, it is tempting to speculate that this general phenomenon might also occur with recently proposed HCC systemic therapeutics (such as regorafenib, approved by FDA in 2017). [29] Further experimentsby using either a drug-resistant cell line or even cancer cells from patientsare clearly warranted to perform an accurate RRI calculation. Likewise, future studies about the underlying mechanism involved in such encouraging observation are fully warranted.…”
Section: Discussionmentioning
confidence: 99%